Systematic Literature Review: Supervisi Kepala Sekolah Terhadap Kinerja Guru Sekolah Dasar - Dedi Romansyah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the role of principal supervision in improving the performance of elementary school teachers. The method used is a Systematic Literature Review (SLR), which identifies, selects, and analyzes relevant studies on academic supervision in the elementary school context. A total of 15 national and international journals were reviewed. The results of the review show that effective supervision by school principals has a significant positive impact on teacher performance, especially in instructional planning, implementation, and evaluation. Strengthening the supervisory and leadership skills of school principals through training and policy support is essential in improving the quality of basic education.